Position and Implementation of the Use of Electronic Medical Records in Proving Medical Crimes in Indonesia - Esti Budi Rahayu; Rahmayanti; Irsyam Risdawati (Equivalent : Journal of Economic, Accounting and Management, 2026)
This study examines the legal status and implementation of electronic medical records in medical criminal proceedings in Indonesia. Digital transformation in the healthcare sector has encouraged healthcare facilities to adopt electronic medical records as part of efforts to improve service quality, efficiency, and health data integration. At the same time, the increasing number of complaints concerning alleged medical malpractice and medical disputes requires the availability of evidentiary instruments capable of recording clinical service processes in a complete, accurate, and accountable manner. Electronic medical records contain essential information such as patient history, physical examinations, diagnoses, therapies, medical procedures, informed consent, medication administration, supporting examination results, and the development of a patient’s condition. Accordingly, electronic medical records have the potential to become a primary source for assessing whether there have been deviations from service standards, negligence, and causal relationships in medical criminal cases.This research employs a normative juridical method with a statutory approach and a conceptual approach. The analysis focuses on regulations governing medical records under the Health Law, ministerial regulations on medical records, as well as the legal regime concerning electronic documents and electronic system security. The findings indicate that electronic medical records have a legally acceptable status as evidence in the form of electronic documents and or documentary evidence, provided that their authenticity and data integrity can be guaranteed. Their implementation in law enforcement processes requires compliance with data security standards, access control mechanisms, standard operating procedures, and the availability of data management traces such as audit trails to ensure that data are not altered without proper authorization.